2020
DOI: 10.1097/ju.0000000000001013
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis Comparing Percutaneous Nephrolithotomy, Retrograde Intrarenal Surgery and Shock Wave Lithotripsy for Lower Pole Renal Stones Less Than 2 cm in Maximum Diameter

Abstract: The aim of the current systematic review and meta-analysis is to provide an answer on which is the most appropriate approach for the management of the lower pole stones with a maximal dimension of 2 cm or less. Materials and Methods: A systematic review was conducted on PubMedÒ, SCOPUSÒ, Cochrane and EMBASEÒ. The PRISMA guidelines and the recommendations of the EAU Guidelines office were followed. Retrograde intrarenal surgery, shock wave lithotripsy and percutaneous nephrolithotomy were considered for compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
(129 reference statements)
3
24
0
Order By: Relevance
“…The rate was significantly higher in PCNL group when compared to ESWL group. This findings has been supported by the study of Montadhar H et al 22 , Elspeth M et al 23 24 Furthermore, mean operation time were significantly higher in PCNL group than ESWL group which is also supported by the study of Kallidonis P 24 and Montadhar H et al 22 The present study showed that the rate of haematuria in PCNL group was significantly higher than ESWL group however in the study of Montadhar H et al 22 and Sheng HanTsai 9 the difference were not significant for rate of haematuria. There were no statistically significant differences between the PCNL and ESWL groups for other post-operative complications such as, blood transfusion, obstruction and fever.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The rate was significantly higher in PCNL group when compared to ESWL group. This findings has been supported by the study of Montadhar H et al 22 , Elspeth M et al 23 24 Furthermore, mean operation time were significantly higher in PCNL group than ESWL group which is also supported by the study of Kallidonis P 24 and Montadhar H et al 22 The present study showed that the rate of haematuria in PCNL group was significantly higher than ESWL group however in the study of Montadhar H et al 22 and Sheng HanTsai 9 the difference were not significant for rate of haematuria. There were no statistically significant differences between the PCNL and ESWL groups for other post-operative complications such as, blood transfusion, obstruction and fever.…”
Section: Discussionsupporting
confidence: 68%
“…, Kallidonis P24 , Bozzin G et al25 , Tayfun S et.al7 and Albala DM26 Based on the above reviews and our result it is revealed that the success rate of PCNL is 84.2 % to 95% while success rate of ESWL is varied form 27% to 67.65%. Meanwhile, study of Gurocak S et al27 showed that lower pole stone treatment by ESWL has shown a large variation for stone free rate from 25% to 85% .…”
supporting
confidence: 51%
See 1 more Smart Citation
“…[10][11][12] Complications such as bleeding, infection, peripheral organ damage, and peripheral exudate were significantly lower than those reported in other related literature studies. 13,14 The low complication rate was closely related to the establishment of an ideal percutaneous renal channel.…”
Section: Discussionmentioning
confidence: 99%
“…As there is no active extraction process involved with this procedure, stone-free rates are generally lower for SWL than for RIRS or PCNL (18,19). There is mounting evidence to suggest that this trend is observed, and perhaps even amplified, when limited to lower pole stones (20,21). This is because the residual fragments after SWL often remain in the lower pole, thereby resulting in recurrent stone formation.…”
Section: Shock Wave Lithotripsymentioning
confidence: 99%